Arthroscopic “Debridement and Implant Retention” With Local Administration of Exebacase (Lysin CF-301) Followed by Suppressive Tedizolid as Salvage Therapy in Elderly Patients for Relapsing Multidrug-Resistant S. epidermidis Prosthetic Knee Infection - Ferry, Tristan; Batailler, Cécile; Souche, Aubin; Cassino, Cara; Chidiac, Christian; Perpoint, Thomas; le Corvaisier, Claire; Josse, Jérôme; Gaillard, Romain; Roger, Julien; Kolenda, Camille; Lustig, Sébastien; et al. (Frontiers in Medicine, 2021)
Exebacase, a recombinantly produced lysin has recently (i) reported proof-of-concept data from a phase II study in S. aureus bacteremia and (ii) demonstrated antibiofilm activity in vitro against S. epidermidis. In patients with relapsing multidrug-resistant (MDR) S. epidermidis prosthetic knee infection (PKI), the only surgical option is prosthesis exchange. In elderly patients who have undergone several revisions, prosthesis explantation could be associated with definitive loss of function and mortality. In our BJI reference regional center, arthroscopic debridement and implant retention with local administration of exebacase (LysinDAIR) followed by suppressive tedizolid as salvage therapy is proposed for elderly patients with recurrent MDR S. epidermidis PKI with no therapeutic option or therapeutic dead end (for whom revision or transfemoral amputation is not feasible and no other oral option is available). Each use was decided in agreement with the French health authority and in accordance with the local ethics committee. A written consent was obtained for each patient. Exebacase (75 mg/mL; 30 mL) was administered directly into the joint during arthroscopy. Four patients (79–89 years old) were treated with the LysinDAIR procedure. All had several previous prosthetic knee revisions without prosthesis loosening. Three had relapsing PKI despite suppressive antibiotics following open DAIR. Two had clinical signs of septic arthritis; the two others had sinus tract. After the LysinDAIR procedure, no adverse events occurred during arthroscopy; all patients received daptomycin 8 mg/kg and linezolid 600 mg bid (4–6 weeks) as primary therapy, followed by tedizolid 200 mg/day as suppressive therapy. At 6 months, recurrence of the sinus tract occurred in the two patients with sinus tract at baseline. After >1 year follow up, the clinical outcome was favorable in the last two patients with total disappearance of clinical signs of septic arthritis even if microbiological persistence was detected in one of them. Exebacase has the potential to be used in patients with staphylococci PKI during arthroscopic DAIR as salvage therapy to improve the efficacy of suppressive antibiotics and to prevent major loss of function.